Laser welding method and laser welding joint

By adjusting the chemical composition of steel and flux, optimizing the laser welding process, forming a needle-shaped ferrite structure, the cracks and insufficient toughness of steel laser welding joints in low temperature environments are solved, and high toughness and excellent welding joint performance are achieved.

CN119630505APending Publication Date: 2025-03-14JFE STEEL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380059296.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-05-08
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has crack problems when laser welding steel in low temperature environments, and the toughness of the welded metal is insufficient, making it difficult to meet the high toughness requirements of the structure to the joints.

Method used

By adjusting the chemical composition of the steel and the composition index X of the flux, the process parameters of laser welding are optimized to form a needle-like ferrite structure and rephasized oxides to improve the toughness of the welded metal.

Benefits of technology

The high toughness of welding metal in a low temperature environment of -20℃ is achieved, ensuring excellent performance of the welded joints and being able to absorb more than 27J of impact energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630505A_ABST
    Figure CN119630505A_ABST
Patent Text Reader

Abstract

Provided are a laser welding method and a laser welded joint for preventing cracks and obtaining a welded joint having excellent toughness of a welded metal. A laser welding method in which steel materials are butted, the surface of the steel material including a weld line is coated with a flux having a predetermined composition, and laser welding is performed therefrom to produce a welded joint, the steel material has a chemical composition containing, in mass%, 0.04 to 0.15% of C, 0.05 to 1.00% of Si, 0.50 to 2.50% of Mn, 0.030% or less of P, 0.020% or less of S, 0.050% or less of Al, 0.050% or less of Ti, 0.010% or less of O, and 0.008% or less of N, with a carbon equivalent Ceq represented by formula (1) satisfying 0.30 to 0.45, with the remainder comprising Fe and unavoidable impurities. Ceq = [C] + [Mn] / 6 + [Si] / 24 + [Cu] / 20 + [Ni] / 40 + [Cr] / 5 + [Mo] / 4 (1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laser welding method and a laser welded joint for steel materials used in a low temperature environment of -20°C. In the present specification, "x to y" indicating a range of numerical values ​​means greater than or equal to x and less than or equal to y, including the boundary values. Background Art

[0002] Compared with general arc welding, high-energy beam welding such as laser welding and electron beam welding has the characteristics of large penetration depth, fast welding speed, and no need for deformation correction after welding. Due to such characteristics, high-energy beam welding is known as an efficient welding method. These high-energy beam weldings are basically fully automatically controlled, so compared with arc welding, they do not require skilled workers. In addition, they have the advantages of less welding deformation and no need for correction work after welding. Therefore, against the background of the rising demand for labor saving and full automation at manufacturing sites in recent years, it is expected that high-energy beam welding will be officially popularized and expanded in the actual construction of thick steel plates.

[0003] On the other hand, the weld metal formed by laser welding is formed by melting and solidifying the base material of the weld using the energy of the laser. Generally, the chemical composition of the weld metal by laser welding is roughly the same as that of the base material, making it difficult to achieve high toughness of the weld metal.

[0004] In this regard, Patent Document 1 discloses adjusting the composition of the base metal and adding oxygen to the shielding gas. In addition, low temperature toughness of the weld metal can be achieved by controlling the element composition ratio Al / O in the weld metal to 0.5 to 1.2.

[0005] In addition, Patent Document 2 discloses a laser welding method and a laser welding flux for welding the surfaces of the materials to be joined by coating them with flux. This technology can achieve deep penetration without using a low vacuum atmosphere, and can also effectively suppress high-temperature cracks. In addition, Patent Document 2 discloses that for the flux component, the total content of the added components selected from manganese dioxide, aluminum oxide, magnesium oxide, titanium oxide and silica sand is set to 30% by mass or more.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2002-121642

[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-82159 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, the method described in Patent Document 1 has problems in weldability, such as increased spatter due to oxygen contained in the shielding gas, increased labor required to remove the spatter, and decreased penetration due to increased plume.

[0012] In addition, the welding method described in Patent Document 2 discloses that the use of flux is effective in suppressing deep penetration and cracking, but cracking cannot be completely suppressed. In addition, since the mechanical properties of the weld metal after laser welding have not been studied, there is a problem that the joint toughness required for the structure may not be ensured.

[0013] In order to solve the above problems, the present invention aims to provide a laser welding method and a laser welded joint for preventing cracks and obtaining a welded joint with excellent toughness of the weld metal. The excellent toughness mentioned here refers to the following: the absorbed energy at -20°C using a V-notch Charpy impact test piece cut from the weld metal in accordance with the provisions of JIS Z 3128:2017 is V E -20 It is 27 J or more. In order to avoid the phenomenon of cracks generated from the weld metal deviating to the base material side, namely FPD (Fracture Path Deviation), a Charpy impact test piece with side grooves was used for the laser welded joint.

[0014] Methods used to solve problems

[0015] In order to achieve the above object, the inventors first conducted an investigation on the chemical composition of the flux, the penetration depth, and the cracking tendency in a laser welding method in which the surface of a steel material including a weld line is coated with flux and then irradiated with laser light to perform joining. As a result, it was found that when the component index X of the flux represented by the following formula (2) is 0.5 or more, both deep penetration and crack suppression can be achieved, and the smaller X is, the deeper the penetration is, but cracks are generated when X is less than 0.5.

[0016] X={(CaO)+(MgO)+(CaF2)+0.5(MnO)+(B2O3)} / {(SiO2)+0.5(Al2O3)+0.5(TiO2)} (2)

[0017] Here, the "(component)" of the flux in the above formula (2) represents the content (mass %) of the component, and is set to 0 when the component is not contained.

[0018] It is also known that a correlation is observed between X and the oxygen content [O] in the laser weld metal, and the smaller X is, the greater the oxygen content [O] in the laser welded weld metal is. As a reason why the penetration depth increases as X decreases, it can be inferred that as the oxygen content [O] in the molten metal increases during laser welding, Marangoni convection strongly acts to generate downward convection. In addition, as a reason why cracks occur when X is less than 0.5, it is inferred that the penetration depth becomes too large relative to the penetration width.

[0019] Next, the effect of microstructure on the toughness of the weld metal portion of the laser welded joint was studied. As a result, it was found that in the weld metal portion with good toughness, a large amount of fine acicular ferrite structure was formed. Further investigation was conducted on the oxides in the weld metal of the laser welded joint where acicular ferrite was formed. As a result, it was found that non-metallic inclusions containing oxides that were multiphased with an amorphous phase and a spinel crystal phase were formed. And it was found that acicular ferrite was formed starting from the non-metallic inclusions.

[0020] As a result of further repeated and intensive studies, it was found that the following adjustments are preferably performed in order to promote the formation of acicular ferrite structure and ensure good toughness.

[0021] First, the carbon equivalent Ceq of the steel material represented by the following formula (1) is adjusted to a range of 0.30 to 0.45, thereby adjusting the hardenability to a level suitable for forming acicular ferrite.

[0022] Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (1)

[0023] Here, "element" of the steel material in the above formula (1) represents the content (mass %) of the element, and is set to 0 when the element is not contained.

[0024] In addition, the oxygen content in the laser welded metal and the Al content and Ti content constituting the spinel crystal phase are optimized. That is, α represented by the following formula (3), which is composed of the Al content [Al] of the steel and the component index X of the above-mentioned flux, is adjusted to a range of 0.2 to 1.1. Furthermore, β represented by the following formula (4), which is composed of the Ti content [Ti] (mass %) of the steel, the amount of TiO2 (TiO2) (mass %) in the flux and the above-mentioned X, is adjusted to a range of 0.2 to 2.5.

[0025] It is understood that by doing this, an oxide in which an amorphous phase and a spinel type crystal phase are dual-phased can be formed, and good toughness can be ensured.

[0026] α = [Al] / (0.025 + 0.05 × log0.1 X) (3)

[0027] β={[Ti]+(TiO2) / 2000} / (0.025+0.05×log 0.1 X) (4)

[0028] The present invention has been completed as a result of further studies based on this finding, and the gist of the present invention is as follows.

[0029] [1] A laser welding method, wherein steel materials are butted against each other, surfaces of the steel materials including a weld line are coated with flux, and laser light is irradiated therefrom to perform joining, wherein:

[0030] The chemical composition of the steel material contains, in mass%, C: 0.04-0.15%, Si: 0.05-1.00%, Mn: 0.50-2.50%, P: 0.030% or less, S: 0.020% or less, Al: 0.050% or less, Ti: 0.050% or less, O: 0.010% or less, and N: 0.008% or less, and optionally contains at least one selected from Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, and B: 0.0030% or less, with the balance being Fe and unavoidable impurities, and

[0031] The carbon equivalent Ceq of the steel material represented by the following formula (1) is in the range of 0.30 to 0.45.

[0032] Furthermore, the composition index X of the flux represented by the following formula (2) is in the range of 0.5 to 2.5.

[0033] α represented by the following formula (3) is in the range of 0.2 to 1.1,

[0034] β represented by the following formula (4) is in the range of 0.2 to 2.5,

[0035] Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (1)

[0036] X={(CaO)+(MgO)+(CaF2)+0.5(MnO)+(B2O3)} / {(SiO2)+0.5(Al2O3)+0.5(TiO2)} (2)

[0037] α = [Al] / (0.025 + 0.05 × log 0.1 X) (3)

[0038] β={[Ti]+(TiO2) / 2000} / (0.025+0.05×log 0.1 X) (4)

[0039] Here, "element" in each of the above formulas represents the content (mass %) of the element in the above steel material, and "component" represents the content (mass %) of the above component in the above flux, and is set to 0 when the element or component is not contained.

[0040] [2] The laser welding method according to [1] above, wherein the steel material has a plate thickness of 6 to 50 mm.

[0041] [3] The laser welding method according to [1] above, wherein the laser welding output power of the laser welding is 5 to 80 kW and the welding speed is 0.3 to 2.0 m / min.

[0042] [4] The laser welding method according to [2] above, wherein the laser welding output power of the laser welding is 5 to 80 kW and the welding speed is 0.3 to 2.0 m / min.

[0043] [5] A laser welded joint obtained by welding using the laser welding method described in any one of [1] to [4] above, wherein:

[0044] The chemical composition of the weld metal contains, in mass%, C: 0.04-0.15%, Si: 0.05-1.00%, Mn: 0.50-2.50%, P: 0.030% or less, S: 0.020% or less, Al: 0.050% or less, Ti: 0.060% or less, O: 0.009-0.050%, and N: 0.010% or less, and optionally contains at least one selected from Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, and B: 0.0030% or less, with the balance being Fe and unavoidable impurities, and

[0045] The carbon equivalent Ceq represented by the following formula (5) is in the range of 0.30 to 0.45,

[0046] The mass ratio of the Al content to the O content in the weld metal is in the range of 0.2 to 1.1.

[0047] The mass ratio of the Ti content to the O content in the weld metal is in the range of 0.2 to 2.5.

[0048] Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (5)

[0049] Here, "element" of the weld metal in the above formula (5) represents the content (mass %) of the element, and is set to 0 when the element is not contained.

[0050] [6] The laser welded joint according to [5], wherein the weld metal has an absorbed energy of a V-notch Charpy impact test at a test temperature of -20°C. V E -20 More than 27J.

[0051] Effects of the Invention

[0052] According to the present invention, a laser welding method can provide a welded joint having excellent joint toughness, and thus exerts a significant effect industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is a schematic diagram showing one embodiment of the laser welding method of the present invention.

[0054] Figure 2 The three-sided schematic diagram shows a test piece with side grooves used in the Charpy impact test of the laser welded joint of the present invention, (a) is a side view, (b) is a front view, and (c) is a bottom view.

[0055] Figure 3 This is a graph showing the relationship between the flux composition index X and the penetration depth in the laser welding method of the present invention. DETAILED DESCRIPTION

[0056] Hereinafter, preferred embodiments of the present invention will be described.

[0057] This embodiment is a laser welding method for producing a welded joint by laser welding butted steel materials. It should be noted that from the viewpoint of weldability, the thickness of the butted steel materials is preferably set to 6 to 50 mm, and more preferably 8 to 45 mm.

[0058] [Chemical composition of steel]

[0059] First, the chemical composition of the steel material used contains, in mass%, C: 0.04-0.15%, Si: 0.05-1.00%, Mn: 0.50-2.50%, P: 0.030% or less, S: 0.020% or less, Al: 0.050% or less, Ti: 0.050% or less, O: 0.010% or less, and N: 0.008% or less. Furthermore, the steel material is set to have a chemical composition in which the carbon equivalent Ceq represented by the following formula (1) satisfies 0.30-0.45 and the balance is Fe and inevitable impurities.

[0060] Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (1)

[0061] Here, "element" of the steel material in the above formula (1) represents the content (mass %) of the element, and is set to 0 when the element is not contained.

[0062] The reasons for limiting the chemical composition of the steel material are as follows: Hereinafter, "%" in the chemical composition means "mass %".

[0063] [C: 0.04~0.15%]

[0064] C is an element effective for increasing the strength of steel at a low price, and in this embodiment, it is necessary to contain 0.04% or more. On the other hand, if it exceeds 0.15%, the weld metal hardens and the toughness decreases. Therefore, the C content is limited to the range of 0.04 to 0.15%. It should be noted that it is preferably in the range of 0.06 to 0.12%. More preferably, it is in the range of 0.07 to 0.10%.

[0065] [Si: 0.05~1.00%]

[0066] Si is an element that acts as a deoxidizing element and helps to improve the strength of steel. In order to obtain such an effect, it is necessary to contain more than 0.05%. On the other hand, if it exceeds 1.00%, a hard second phase (striped martensite) is formed in the weld metal portion, and the toughness of the weld metal portion is reduced. Therefore, the Si content is limited to the range of 0.05 to 1.00%. It should be noted that the range is preferably 0.10 to 0.80%. More preferably, it is in the range of 0.20 to 0.60%.

[0067] [Mn: 0.50~2.50%]

[0068] Mn is an element useful for improving the strength of steel. In order to obtain such an effect, it is necessary to contain 0.50% or more. On the other hand, if it exceeds 2.50%, the weld metal hardens and the toughness decreases. Therefore, the Mn content is limited to the range of 0.50 to 2.50%. It should be noted that it is preferably in the range of 0.80 to 2.00%. More preferably, it is in the range of 1.00 to 1.80%.

[0069] [P: 0.030% or less]

[0070] P is an element that reduces the toughness of steel and induces high-temperature cracking of weld metal. Therefore, in this embodiment, it is preferably reduced as much as possible. On the other hand, it is allowed when the P content is 0.030% or less. Therefore, the P content is limited to 0.030% or less. It should be noted that excessive reduction of P leads to a rise in refining costs. Therefore, the P content is preferably adjusted to 0.005% or more. More preferably, it is in the range of 0.006 to 0.020%.

[0071] [S: 0.020% or less]

[0072] S forms MnS in the steel, becomes elongated MnS that extends during rolling, and becomes the main cause of lamellar tearing. Therefore, in this embodiment, it is preferably reduced as much as possible. On the other hand, it is allowed when the S content is 0.020% or less. Therefore, the S content is limited to 0.020% or less. It should be noted that excessive reduction of S leads to a rise in refining costs. Therefore, the S content is preferably adjusted to 0.003% or more. More preferably, it is in the range of 0.004 to 0.015%.

[0073] [Al: 0.050% or less]

[0074] If more than 0.050% Al is contained, the toughness of the steel (parent material) is reduced due to solid solution Al. Therefore, the Al content is limited to less than 0.050%. On the other hand, Al acts as a deoxidizing element and has the effect of contributing to the refinement of the microstructure and improving the toughness of the steel. In order to obtain such an effect, it is preferably contained at least 0.004%. It should be noted that the range of 0.006 to 0.042% is more preferred. The range of 0.010 to 0.038% is further preferred.

[0075] Furthermore, in order to form an acicular ferrite structure that contributes to high toughness of the weld metal, first, the Al content (hereinafter also referred to as [Al]) in the weld metal needs to be controlled. W ) and the oxygen content in the weld metal (hereinafter also referred to as [O] W ) mass ratio [Al] W / [O] WTo this end, the Al content of the steel (hereinafter referred to as [Al] B ) and the chemical composition of the flux are adjusted to an appropriate range. The relationship between them will be described later.

[0076] [Ti: 0.050% or less]

[0077] When Ti is added to the steel, Ti-based oxides are formed in the weld metal, which become the nuclei for the formation of acicular ferrite. In order to obtain such an effect, it is necessary to add 0.003% or more. However, Ti can also be added to the weld metal from the flux, so it is not necessarily necessary to add Ti to the steel. On the other hand, if the Ti content of the steel exceeds 0.050%, the toughness of the steel is deteriorated due to the solid solution of Ti. Therefore, the Ti content is limited to less than 0.050%. It should be noted that it is preferably less than 0.040%. More preferably, it is in the range of 0.005 to 0.040%.

[0078] In order to form an acicular ferrite structure, it is necessary to control the Al content in the weld metal as described above and to control the Ti content in the weld metal (hereinafter also referred to as [Ti] W ) and oxygen content [O] W Mass ratio [Ti] W / [O] W To this end, the Ti content of the steel (hereinafter referred to as [Ti] B ), the TiO2 content of the flux (hereinafter also referred to as (TiO2)) and the chemical composition of the flux are adjusted to an appropriate range. The relationship between them will be described later.

[0079] [O (oxygen): 0.010% or less]

[0080] O (oxygen) forms non-metallic inclusions in the form of oxides in steel, which becomes the starting point of destruction. Therefore, in this embodiment, it is preferably reduced as much as possible. On the other hand, the O (oxygen) content is allowed when it is less than 0.010%, so it is limited to less than 0.010%. It should be noted that excessive reduction of O (oxygen) leads to a rise in refining costs, so the O (oxygen) content is preferably adjusted to more than 0.002%. More preferably, it is in the range of 0.003 to 0.008%.

[0081] [N: 0.008% or less]

[0082] N is an element mixed as an impurity. Solid solution N reduces toughness, so it is preferably reduced as much as possible. On the other hand, N content is allowed when it is 0.008% or less. Therefore, the N content is limited to 0.008% or less. It should be noted that excessive reduction of N leads to a rise in refining costs, so the N content is preferably adjusted to 0.002% or more. More preferably, it is in the range of 0.003 to 0.007%.

[0083] [Optional composition]

[0084] The above chemical composition is the basic composition of the steel material used in this embodiment. In this embodiment, at least one selected from the following chemical compositions may be further contained as an optional composition based on the above basic composition as needed. The chemical composition is: Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, B: 0.0030% or less.

[0085] [Cu: 1.00% or less]

[0086] If more than 1.00% Cu is contained, red hot brittleness is sometimes exhibited, surface cracks of the steel material are generated, and the manufacturability of the steel material is reduced. Therefore, when contained, the Cu content is preferably set to 1.00% or less. On the other hand, Cu is an element that increases the strength of the steel material and improves the corrosion resistance. In order to obtain such an effect, it is preferably contained at 0.10% or more. More preferably, it is in the range of 0.15 to 0.90%.

[0087] [Ni: 2.00% or less]

[0088] If Ni is contained in an amount exceeding 2.00%, the manufacturing cost will be increased. Therefore, when Ni is contained, the Ni content is preferably set to 2.00% or less. On the other hand, Ni is an element that increases the strength of the steel material without reducing the toughness of the steel material and improves the toughness of the weld heat affected zone. In order to obtain such an effect, Ni is preferably contained in an amount of 0.10% or more. More preferably, it is in the range of 0.20 to 1.80%.

[0089] [Cr: 1.00% or less]

[0090] If more than 1.00% Cr is contained, the toughness of the steel material may be reduced. Therefore, when contained, the Cr content is preferably set to 1.00% or less. On the other hand, Cr is an element that improves the strength of the steel material. In order to obtain such an effect, it is preferably contained at least 0.10%. More preferably, it is in the range of 0.15 to 0.90%.

[0091] [Mo: 1.00% or less]

[0092] If Mo is contained in an amount exceeding 1.00%, the toughness of the steel may be reduced. Therefore, when Mo is contained, the Mo content is preferably set to 1.00% or less. On the other hand, Mo is an element that improves the strength of the steel, and in order to obtain such an effect, it is preferably contained in an amount of 0.10% or more. More preferably, it is in the range of 0.15 to 0.90%.

[0093] [Nb: 0.20% or less]

[0094] If Nb is contained in an amount exceeding 0.20%, the toughness of the steel may be reduced. Therefore, when Nb is contained, the Nb content is preferably set to 0.20% or less. On the other hand, Nb is an element that improves the strength of the steel by improving hardenability. In order to obtain such an effect, it is preferably contained in an amount of 0.01% or more. More preferably, it is in the range of 0.02 to 0.16%.

[0095] [V: 0.20% or less]

[0096] If V is contained in an amount exceeding 0.20%, the toughness of the steel may be reduced. Therefore, when V is contained, it is preferably set to 0.20% or less. On the other hand, V is an element that precipitates fine carbides and improves the strength of the steel. In order to obtain such an effect, it is preferably contained in an amount of 0.02% or more. More preferably, it is in the range of 0.04 to 0.16%.

[0097] [Ca: 0.005% or less]

[0098] If more than 0.005% of Ca is contained, coarse CaS may increase, which may become the starting point of destruction and reduce the toughness of the steel. Therefore, when Ca is contained, the Ca content is preferably set to 0.005% or less. On the other hand, Ca is an element that combines with S to form spherical CaS, thereby helping to control the shape of sulfides, and prevents the occurrence of lamellar tearing when tensile stress acts in the thickness direction of the plate. In order to obtain such an effect, it is preferred to contain more than 0.001% of Ca. More preferably, it is in the range of 0.001 to 0.004%.

[0099] [REM: 0.050% or less]

[0100] If more than 0.050% REM (rare earth element) is contained, REM segregated at the austenite grain boundary sometimes reduces ductility, becomes the main cause of cracks, and reduces the manufacturability of the steel. Therefore, when contained, the REM content is preferably set to 0.050% or less. On the other hand, REM combines with S to form sulfides. The sulfide has ferrite nucleation ability, forms ferrite grains from within austenite grains, and thus contributes to the refinement of the microstructure. In order to obtain such an effect, it is preferred to contain more than 0.002% REM. More preferably, it is in the range of 0.005 to 0.040%.

[0101] [B: 0.0030% or less]

[0102] If more than 0.0030% B is contained, segregation sometimes occurs at the austenite grain boundary during casting solidification, forming a liquid phase, inducing the generation of cracks. Therefore, when contained, the B content is preferably set to 0.0030% or less. On the other hand, B combines with N to form BN in the austenite grains. The BN formed in the heat-affected zone becomes a ferrite nucleation site, so the microstructure is refined, which helps to improve the toughness of the heat-affected zone. In order to obtain such an effect, it is preferred to contain 0.0005% or more B. More preferably, it is in the range of 0.0008 to 0.0025%.

[0103] [Remainder composition]

[0104] The balance other than the above chemical composition is composed of Fe and inevitable impurities. It should be noted that as inevitable impurities, H, Mg, Zn, Re, Co, Sb, and Bi can be exemplified, and a total of 0.01% or less is allowed. Moreover, the inclusion of elements below the preferred lower limit of the elements described in the above selected composition will not have an adverse effect on the laser welded joint, so it is allowed. In addition, as long as the above basic composition and selected composition are met, elements other than these may be contained, and such an embodiment is also included in the technical scope of the present invention.

[0105] [Carbon equivalent Ceq: 0.30~0.45]

[0106] In the present embodiment, it is important that the carbon equivalent Ceq represented by the following formula (1) is in the range of 0.30 to 0.45.

[0107] Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (1)

[0108] Here, "element" of the steel material in the above formula (1) represents the content (mass %) of the element, and is set to 0 when the element is not contained.

[0109] The inventors have conducted intensive studies to solve the above problems and have found that it is effective to adjust the carbon equivalent Ceq represented by the above formula (1) to a range of 0.30 to 0.45 in order to ensure the strength and toughness of the steel.

[0110] Carbon equivalent Ceq is a value obtained by converting the chemical composition contained in the steel into carbon (C). In order to ensure the strength and toughness of the steel, Ceq needs to be set in the range of 0.30 to 0.45. If Ceq is less than 0.30, the target steel strength cannot be obtained. On the other hand, if Ceq is greater than 0.45, the strength of the steel becomes too high and the toughness decreases. The preferred range is 0.34 to 0.42.

[0111] [Flux]

[0112] The flux used in this embodiment does not need to be particularly limited. Any of the commonly known molten flux or bonding flux can be used. As the chemical composition of the flux, a powder material containing the chemical components listed below can be used. For example, CaO: 8.0-28.0%, MgO: 4.0-11.0%, CaF2: 3.5-30.0%, MnO: 6.0-16.0%, B2O3: 1.0% or less, SiO2: 13.0-40.0%, Al2O3: 2.0-19.0%, TiO2: 4.0-20.0%, etc. can be listed. However, in this embodiment, the flux is not limited to this.

[0113] Next, the reason why the component index X of the flux represented by the following formula (2) is limited to 0.5 to 2.5 will be described.

[0114] X={(CaO)+(MgO)+(CaF2)+0.5(MnO)+(B2O3)} / {(SiO2)+0.5(Al2O3)+0.5(TiO2)} (2)

[0115] Here, the "(component)" of the flux in the above formula (2) represents the content (mass %) of the component, and is set to 0 when the component is not contained.

[0116] Figure 3 This is a graph showing the results of investigating the relationship between the flux component index X and the penetration depth during laser welding. As described above, the oxygen content in the flux components is correlated with the penetration depth. The smaller X is, the greater the oxygen content and the greater the penetration depth. However, if X is less than 0.5, the penetration depth becomes too large and cracks occur. On the other hand, if X is greater than 2.5, the oxygen content in the weld metal after laser welding decreases, and the amount of oxides required to form acicular ferrite is insufficient. Therefore, X is limited to the range of 0.5 to 2.5. Preferably, it is in the range of 0.7 to 2.2.

[0117] [Chemical composition of weld metal]

[0118] Next, the chemical composition of the weld metal formed by laser welding according to the present embodiment will be described.

[0119] The chemical composition of the weld metal is basically the same as that of the steel material, but part of the chemical composition of the flux used in laser welding is mixed in.

[0120] The basic chemical composition of the weld metal contains C: 0.04-0.15%, Si: 0.05-1.00%, Mn: 0.50-2.50%, P: 0.030% or less, S: 0.020% or less, Al: 0.050% or less, Ti: 0.060% or less, O: 0.009-0.050%, N: 0.010% or less. Furthermore, the weld metal is set to have a chemical composition in which the carbon equivalent Ceq represented by the following formula (5) satisfies 0.30-0.45 and the balance is Fe and inevitable impurities.

[0121] Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (5)

[0122] Here, "element" of the weld metal in the above formula (5) represents the content (mass %) of the element, and is set to 0 when the element is not contained.

[0123] In addition to the above basic composition, at least one selected from the following chemical compositions may be contained: Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, and B: 0.0030% or less.

[0124] [C: 0.04~0.15%]

[0125] C is an element effective for improving the strength of the weld metal, and in the present embodiment, it is preferably contained at 0.04% or more. On the other hand, if it is contained in an amount exceeding 0.15%, the weld metal may harden and the toughness may decrease. Therefore, the C content is preferably set to a range of 0.04 to 0.15%. A range of 0.06 to 0.12% is more preferred. A range of 0.07 to 0.10% is further preferred.

[0126] [Si: 0.05~1.00%]

[0127] Si is an element that acts as a deoxidizing element and helps to improve the strength of the weld metal. In order to obtain such an effect, it is preferably contained at 0.05% or more. On the other hand, if it exceeds 1.00%, a hard second phase (striped martensite) is sometimes formed in the weld metal, and the toughness of the weld metal is reduced. Therefore, the Si content is preferably set to a range of 0.05 to 1.00%. More preferably, it is in the range of 0.10 to 0.80%. More preferably, it is in the range of 0.20 to 0.60%.

[0128] [Mn: 0.50~2.50%]

[0129] Mn is an element useful for improving the strength of the weld metal. In order to obtain such an effect, it is preferably contained at least 0.50%. On the other hand, if it exceeds 2.50%, the weld metal is hardened and the toughness is reduced. Therefore, the Mn content is preferably set to a range of 0.50 to 2.50%. More preferably, it is in the range of 0.80 to 2.00%. More preferably, it is in the range of 1.00 to 1.80%.

[0130] [P: 0.030% or less]

[0131] P is an element that reduces the toughness of the weld metal and induces high temperature cracking of the weld metal. Therefore, in this embodiment, it is preferably reduced as much as possible. P content is allowed when it is less than 0.030%. Therefore, the P content is preferably set to less than 0.030%. It should be noted that excessive reduction of P leads to an increase in the manufacturing cost of steel. Therefore, the P content is more preferably adjusted to more than 0.005%. More preferably, it is in the range of 0.006 to 0.020%.

[0132] [S: 0.020% or less]

[0133] S segregates during the solidification of the weld metal, causing the weld metal to have a low melting point, thus inducing high temperature cracks. Therefore, in this embodiment, it is preferably reduced as much as possible. An S content of 0.020% or less is permissible. Therefore, the S content is preferably set to 0.020% or less. It should be noted that excessive reduction of S leads to an increase in the manufacturing cost of steel. Therefore, the S content is more preferably adjusted to 0.003% or more. More preferably, it is in the range of 0.004 to 0.015%.

[0134] [Al: 0.050% or less]

[0135] If more than 0.050% Al is contained, the toughness of the weld metal is reduced due to solid solution Al. Therefore, the Al content is preferably set to 0.050% or less. On the other hand, Al acts as a strong deoxidizing element, so it preferentially combines with O (oxygen) to form an oxide. In addition, Al promotes the formation of spinel-type crystal phases in oxides and contributes to the formation of acicular ferrite structure. In order to obtain such an effect, it is preferably contained at least 0.004%. More preferably, it is in the range of 0.006 to 0.042%. More preferably, it is in the range of 0.010 to 0.038%.

[0136] In order to achieve high toughness of the weld metal, it is preferable to control the [Ti] W / [O] W The mass ratio of Al content to oxygen content in the weld metal [Al] W / [O] W The control range is 0.2 to 1.1. This is because in [Al] W / [O] W In the case of this range, a spinel oxide which is a crystal phase effective for forming acicular ferrite can be formed. W / [O] W If the ratio is less than 0.2, the oxide becomes amorphous. On the other hand, if it is greater than 1.1, the oxide becomes entirely Al2O3 as a crystalline phase. W / [O] W To control within this range, α represented by the following formula (3) is preferably controlled within the range of 0.2 to 1.1, and more preferably within the range of 0.3 to 1.0.

[0137] α=[Al] B / (0.025+0.05×log 0.1 X) (3)

[0138] Here, [Al] B is the Al content (mass %) of the steel material, and X is the flux composition index calculated by the above formula (2).

[0139] [Ti: 0.060% or less]

[0140] If the weld metal contains more than 0.060% Ti, the toughness of the weld metal deteriorates due to the solid solution Ti. Therefore, the Ti content is preferably set to 0.060% or less. On the other hand, Ti-based oxides are formed in the weld metal, which become the nucleus for the formation of acicular ferrite. In order to obtain such an effect, it is preferably contained at least 0.003%. It should be noted that it is more preferably 0.050% or less. It is further preferably in the range of 0.006 to 0.040%.

[0141] In order to form an acicular ferrite structure, it is preferable to set the mass ratio of Ti content to oxygen content in the weld metal to [Ti] W / [O] W is controlled within the range of 0.2 to 2.5. This is because, in [Ti] W / [O] W In the case of this range, a spinel oxide which is a crystal phase effective for the formation of acicular ferrite can be formed. W / [O] W If the ratio is less than 0.2, the oxide becomes an amorphous single phase. On the other hand, if it is greater than 2.5, the oxide becomes entirely TiO2 as a crystalline phase. W / [O] W To control within this range, β represented by the following formula (4) is preferably controlled within the range of 0.2 to 2.5, and more preferably within the range of 0.3 to 2.0.

[0142] β = {[Ti] B +(TiO2) / 2000} / (0.025+0.05×log 0.1 X) (4)

[0143] Here, [Ti] B is the Ti content (mass %) of the steel, (TiO2) is the TiO2 content (mass %) in the flux, and X is the flux composition index calculated by the above formula (2).

[0144] [O (oxygen): 0.009~0.050%]

[0145] O (oxygen) forms oxides in the weld metal. If [Al] W / [O] W Control it to the range of 0.2 to 1.1, and then [Ti] W / [O] W If it is controlled to be in the range of 0.2 to 2.5, an oxide in which an amorphous phase and a spinel-type crystal phase are complexed can be formed. Moreover, a needle-shaped ferrite with the oxide as the nucleation starting point can be formed, which can achieve an improvement in toughness. In order to obtain such an effect, it is preferably contained at least 0.009%. On the other hand, when the O (oxygen) content exceeds 0.050%, the oxide coarsens and becomes the starting point for the destruction. Therefore, in the present embodiment, the O (oxygen) content is preferably set to the range of 0.009 to 0.050%. More preferably, it is in the range of 0.010 to 0.040%.

[0146] [N: 0.010% or less]

[0147] N is an element mixed as an impurity. Solid solution N reduces toughness, so it is preferably reduced as much as possible. N content is allowed when it is 0.010% or less. Therefore, N content is preferably set to 0.010% or less. More preferably, it is 0.008% or less.

[0148] [Optional composition]

[0149] The above chemical composition is the basic composition of the weld metal of the present embodiment. In the present embodiment, in addition to the above basic composition, at least one selected from the following chemical compositions may be further contained as an optional composition as needed. The chemical composition is: Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, B: 0.0030% or less.

[0150] [Cu: 1.00% or less]

[0151] If more than 1.00% Cu is contained, red hot brittleness may occur, and surface cracks may occur in the weld metal. Therefore, when Cu is contained, the Cu content is preferably set to 1.00% or less. On the other hand, Cu is an element that increases the strength of the weld metal and improves the corrosion resistance. In order to obtain such effects, it is preferably contained at 0.10% or more. More preferably, it is in the range of 0.15 to 0.90%.

[0152] [Ni: 2.00% or less]

[0153] If Ni is contained in an amount exceeding 2.00%, the manufacturing cost of the steel material will increase. Therefore, when Ni is contained, the Ni content is preferably set to 2.00% or less. On the other hand, Ni is an element that improves the strength of the weld metal without reducing the toughness of the weld metal. In order to obtain such an effect, it is preferably contained in an amount of 0.10% or more. More preferably, it is in the range of 0.20 to 1.80%.

[0154] [Cr: 1.00% or less]

[0155] If Cr is contained in an amount exceeding 1.00%, the toughness of the weld metal may be reduced. Therefore, when contained, the Cr content is preferably set to 1.00% or less. On the other hand, Cr is an element that improves the strength of the weld metal, and in order to obtain such an effect, it is preferably contained in an amount of 0.10% or more. More preferably, it is in the range of 0.15 to 0.90%.

[0156] [Mo: 1.00% or less]

[0157] If Mo is contained in an amount exceeding 1.00%, the toughness of the weld metal may be reduced. Therefore, when Mo is contained, the Mo content is preferably set to 1.00% or less. On the other hand, Mo is an element that improves the strength of the weld metal, and in order to obtain such an effect, it is preferably contained in an amount of 0.10% or more. More preferably, it is in the range of 0.15 to 0.90%.

[0158] [Nb: 0.20% or less]

[0159] If Nb exceeds 0.20%, the toughness of the weld metal may be reduced. Therefore, when Nb is contained, the Nb content is preferably set to 0.20% or less. On the other hand, Nb is an element that improves the strength of the weld metal by improving hardenability. In order to obtain such an effect, it is preferably contained at 0.01% or more. More preferably, it is in the range of 0.02 to 0.16%.

[0160] [V: 0.20% or less]

[0161] If V is contained in an amount exceeding 0.20%, the toughness of the weld metal may be reduced. Therefore, when V is contained, the V content is preferably set to 0.20% or less. On the other hand, V is an element that precipitates fine carbides and improves the strength of the weld metal. In order to obtain such an effect, it is preferably contained in an amount of 0.02% or more. More preferably, it is in the range of 0.04 to 0.16%.

[0162] [Ca: 0.005% or less]

[0163] When more than 0.005% of Ca is contained, coarse CaS is formed, which becomes the starting point of destruction. Therefore, when contained, the Ca content is preferably set to 0.005% or less. On the other hand, Ca combines with S to form spherical CaS and becomes a nucleation site, which helps to form a needle-shaped ferrite structure. In order to obtain such an effect, it is preferably contained at least 0.001%. More preferably, it is in the range of 0.002 to 0.004%.

[0164] [REM: 0.050% or less]

[0165] If more than 0.050% REM (rare earth element) is contained, REM segregated at the austenite grain boundary sometimes reduces ductility and becomes the main cause of cracks. Therefore, when contained, the REM content is preferably set to 0.050% or less. On the other hand, REM combines with S to form sulfides. The sulfide has ferrite nucleation ability and forms ferrite grains from within austenite grains, thereby contributing to the refinement of the microstructure. In order to obtain such an effect, REM preferably contains 0.002% or more. More preferably, it is in the range of 0.005 to 0.040%.

[0166] [B: 0.0030% or less]

[0167] If more than 0.0030% B is contained, the hardenability becomes excessive, and hard striped martensite is formed between the acicular ferrite lattices, so the toughness deteriorates. Therefore, when contained, the B content is preferably set to 0.0030% or less. On the other hand, B segregates at the austenite grain boundaries in the weld metal, thereby suppressing the low-toughness grain boundary ferrite and promoting the formation of acicular ferrite structure. In addition, it combines with N to form BN in the austenite grains, which becomes the acicular ferrite nucleation site, so the microstructure is refined, which helps to improve the toughness of the weld metal. In order to obtain such an effect, it is preferably contained more than 0.0005% B. More preferably, it is in the range of 0.0008 to 0.0025%.

[0168] [Remainder composition]

[0169] The balance other than the chemical composition of the weld metal described above is composed of Fe and inevitable impurities. It should be noted that as inevitable impurities, H, Mg, Zn, Re, Co, Sb, and Bi are mainly mixed from steel and flux, and are allowed when the total is less than 0.01%. Moreover, the inclusion of the elements below the preferred lower limit described in the above-mentioned selected composition will not have an adverse effect on the laser welded joint, so it is allowed. In addition, as long as the above-mentioned basic composition and selected composition are met, elements other than these may be contained, and such an embodiment is also included in the technical scope of the present invention.

[0170] [Laser welding method]

[0171] The laser welding used in this embodiment is as follows Figure 1 As shown, the joint interfaces 4 of the steel materials 1 are butted against each other, the surface of the steel material 1 including the weld line 4 is coated with flux 2, and laser light 3 is irradiated therefrom to perform the joining, and the symbol WD indicates the welding direction. The laser used does not need to be particularly limited, but it is preferably set to be welding using a fiber laser that is easy to increase the output power while maintaining the beam quality.

[0172] The welding conditions of laser welding are preferably selected appropriately according to the plate thickness of the material to be welded. For example, when the plate thickness is in the range of 6 mm or more and less than 12 mm, it is preferably set to a laser output power of 5 to 10 kW and a welding speed of 0.8 to 2.0 m / min. When the plate thickness is in the range of 12 mm or more and less than 24 mm, it is preferably set to a laser output power of 8 to 30 kW and a welding speed of 0.6 to 1.4 m / min. When the plate thickness is in the range of 24 mm or more and less than 36 mm, it is preferably set to a laser output power of 20 to 60 kW and a welding speed of 0.5 to 1.0 m / min. When the plate thickness is in the range of 36 mm to 50 mm, it is preferably set to a laser output power of 40 to 80 kW and a welding speed of 0.3 to 0.8 m / min.

[0173] Example

[0174] Molten metals having the chemical compositions shown in Table 1 were melted in an arc melting furnace and poured into a mold to form steel ingots, which were then hot-rolled to obtain steel materials having a thickness of 50 mm.

[0175]

[0176] In addition, raw material powders were blended to have the chemical composition shown in Table 2, and sodium silicate was used as a binder and kneaded together, followed by granulation and calcination at 1000° C. to obtain flux. The particle size of the flux was set to 0.1 to 2.0 mm.

[0177]

[0178] Two test plates were prepared from each of the obtained steel materials. The lateral ends of the two test plates were butted together to form an I-shaped groove with a root gap of 0 mm, and the surface of the steel material 1 including the weld line 4 was coated with each flux 2, and the laser 3 was irradiated from above to produce a laser welded joint. It should be noted that the lateral end surface of the test plate to be butted was subjected to cutting. The combinations of steel materials and fluxes used in the production of each joint are shown in Table 3.

[0179]

[0180] The laser welding conditions were set as follows: using fiber laser, laser output power: 50 kW, welding speed: 0.6 m / min, defocus distance (distance from the surface of the material to be joined to the inside): -40 mm, laser incident angle: 10° (sweep angle), flux spreading height: 10 mm.

[0181] For each welded joint obtained, the cross-section macrostructure was cut to investigate the penetration depth and the presence of cracks. Specifically, regarding the penetration depth, the length (mm) from the steel material surface of the welded joint cross section to the position where the weld metal had the maximum penetration depth was measured. Regarding the presence of cracks, the case where cracks were observed in the weld metal cross section was judged as "presence" of cracks, and the case where cracks were not observed was judged as "no" cracks.

[0182] The obtained results are shown in Table 4.

[0183] In addition, chips were collected from a range of φ1 mm at 20 mm from the surface of the test plate at the center of the width of the weld metal, and elemental analysis was performed by wet analysis. The obtained results are collectively shown in Table 4.

[0184] In addition, a Charpy impact test piece (V-notch) was cut from the center of the width of the weld metal at a position 20 mm from the surface of the test plate of the welded joint, and a Charpy impact test was performed at a test temperature of -20°C to determine the absorbed energy. V E -20 (J) It should be noted that in order to avoid the phenomenon of crack deviation (FPD) in which the crack is biased toward the base material side, the V-notch Charpy impact test piece used is set to Figure 2 The obtained results are shown in Table 4.

[0185]

[0186] In all the examples of the invention, no cracks were generated, and the absorbed energy of the Charpy impact test at a test temperature of -20°C for the weld metal was V E -20 It is a welded joint with a strength of more than 27J and excellent toughness and quality.

[0187] On the other hand, in the comparative examples outside the scope of the present invention, cracks occurred or the impact toughness of the weld metal was insufficient, and the target weld joint was not obtained.

[0188] Explanation of symbols

[0189] 1Steel

[0190] 2. Flux

[0191] 3 Laser

[0192] 4Welding line (joining interface)

Claims

1. A laser welding method, which is a method of joining steel materials together, coating the surfaces of the steel materials including the weld line with flux, and irradiating the surfaces with laser light, wherein: The chemical composition of the steel material contains, in mass%, C: 0.04-0.15%, Si: 0.05-1.00%, Mn: 0.50-2.50%, P: 0.030% or less, S: 0.020% or less, Al: 0.050% or less, Ti: 0.050% or less, O: 0.010% or less, and N: 0.008% or less, and optionally contains at least one selected from Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, and B: 0.0030% or less, with the balance being Fe and unavoidable impurities, and The carbon equivalent Ceq of the steel material represented by the following formula (1) is in the range of 0.30 to 0.

45. Furthermore, the flux has a component index X represented by the following formula (2) in the range of 0.5 to 2.

5. α represented by the following formula (3) is in the range of 0.2 to 1.1, β represented by the following formula (4) is in the range of 0.2 to 2.5, Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (1) X={(CaO)+(MgO)+(CaF2)+0.5(MnO)+(B2O3)} / {(SiO2)+0.5(Al2O3)+0.5(TiO2)} (2) α=[A] / (0.025+0.05×log 0.1 X) (3) β={[Ti]+(TiO2) / 2000} / (0.025+0.05×log 0.1 X) (4) Here, "element" in each of the above formulas represents the content (mass %) of the element in the steel material, and "component" represents the content (mass %) of the component in the flux, and is set to 0 when the element or component is not contained.

2. The laser welding method according to claim 1, wherein: The steel plate has a thickness of 6 to 50 mm.

3. The laser welding method according to claim 1, wherein: The laser welding output power of the laser welding is in the range of 5 to 80 kW, and the welding speed is in the range of 0.3 to 2.0 m / min.

4. The laser welding method according to claim 2, wherein: The laser welding output power of the laser welding is in the range of 5 to 80 kW, and the welding speed is in the range of 0.3 to 2.0 m / min.

5. A laser welded joint obtained by welding using the laser welding method according to any one of claims 1 to 4, wherein: The chemical composition of the weld metal contains, in mass%, C: 0.04-0.15%, Si: 0.05-1.00%, Mn: 0.50-2.50%, P: 0.030% or less, S: 0.020% or less, Al: 0.050% or less, Ti: 0.060% or less, O: 0.009-0.050%, and N: 0.010% or less, and optionally contains at least one selected from Cu: 1.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, Nb: 0.20% or less, V: 0.20% or less, Ca: 0.005% or less, REM: 0.050% or less, and B: 0.0030% or less, with the balance being Fe and unavoidable impurities, and The carbon equivalent Ceq represented by the following formula (5) is in the range of 0.30 to 0.45, The mass ratio of the Al content to the O content in the weld metal is in the range of 0.2 to 1.

1. The mass ratio of the Ti content to the O content in the weld metal is in the range of 0.2 to 2.5, Ceq=[C]+[Mn] / 6+[Si] / 24+[Cu] / 20+[Ni] / 40+[Cr] / 5+[Mo] / 4 (5) Here, "element" of the weld metal in the above formula (5) represents the content (mass %) of the element, and is set to 0 when the element is not contained.

6. The laser welded joint according to claim 5, wherein: The weld metal is subjected to a V-notch Charpy impact test at a test temperature of -20°C. V E -20 More than 27J.

Citation Information

Patent Citations

  • Laser welded joint of steel and laser welding method

    JP2002121642A

  • Laser welding method and flux for laser welding

    JP2020082159A